Specific growth rate of bifidobacteria cultured on different sugars - Rada, V; Bartonová, J; Vlková, E (Folia microbiologica, 2002)
The ability of six bifidobacterial strains (3 of human origin and 3 isolates from fermented milk products) to utilize glucose, lactose, melezitose, sucrose, raffinose, and stachyose was determined. Dairy-related bifidobacterial strains were identified as Bifidobacterium animalis (2 strains) or as B. pseudolongum (1 strain). Human strains included B. longum (2 strains) and B. breve (1 strain). All strains fermented lactose, sucrose, raffinose, and stachyose. Melezitose was utilized only by B. longum. B. pseudolongum did not ferment either glucose or melezitose. All isolates had a higher specific growth rate on raffinose and stachyose than on glucose. Dairy strain grew slowly on glucose compared to human strains.
Keywords: Oligosaccharides; feces; Humans; Carbohydrate Metabolism; mléčné výrobky; Bacteriological Techniques; lidé; zvířata; metabolismus sacharidů; glukosa; Culture Media; kultivační média; Feces; Glucose; Dairy Products; oligosacharidy; Animals; Bifidobacterium; bakteriologické techniky